1956
DOI: 10.1180/minmag.1956.031.234.03
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the mica polymorphs

Abstract: SummaryAn experimental and theoretical study has been made in order to determine the number and the structure of the possible polymorphs and to determine the structural relations between them. The simplest structures are 1M, 2M1, 2M2, 3T, 20, and 6H polymorphs, and more complicated types can be developed. Some of the previously described polymorphs were not contained in the theoretical list and were re-examined. The 6M structure was found to be a 2M2 polymorph, the 6-layer triclinic type was found to be a 2M1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(94 citation statements)
references
References 13 publications
4
90
0
Order By: Relevance
“…The observations summarized above are consistent with conclusions reached from structure refinements of layer silicates by Smith and Yoder (1956), Zvyagin (1967), and others. Although Bailey (1975) questioned the validity of using ideal space groups in these structure refinements (and suggested that tetrahedral order may be more prevalent than previous studies indicate), it nevertheless appears reasonable to assume on the basis of all the various data currently available that in most cases tetrahedral disorder prevails in low-temperature layer silicates other than margarite and rare polytypes such as phengite 2M2 and muscovite 3T.…”
Section: Compositional Variation and Substitutional Order/disorder Insupporting
confidence: 80%
“…The observations summarized above are consistent with conclusions reached from structure refinements of layer silicates by Smith and Yoder (1956), Zvyagin (1967), and others. Although Bailey (1975) questioned the validity of using ideal space groups in these structure refinements (and suggested that tetrahedral order may be more prevalent than previous studies indicate), it nevertheless appears reasonable to assume on the basis of all the various data currently available that in most cases tetrahedral disorder prevails in low-temperature layer silicates other than margarite and rare polytypes such as phengite 2M2 and muscovite 3T.…”
Section: Compositional Variation and Substitutional Order/disorder Insupporting
confidence: 80%
“…Unlike Z vectors, these vectors do not pass through any cation site in the O sheet. Therefore, stacking vectors of Smith & Yoder (1956) cannot distinguish between M1 and M2 layers and they too correspond to the homo-octahedral approximation.³ Both the M layer and the TS unit layers have the origin in the interlayer region. However, TS unit layers are shifted along [001] by half the thickness of the M layer ( Fig.…”
Section: Symbolic Description and Layer Orientationmentioning
confidence: 99%
“…The stacking sequence of mica polytypes is quite often described by means of the stacking vectors according to the original de®nition of Smith & Yoder (1956), i.e. the (001) projection of vectors connecting two nearest interlayer cations on the two sides of a layer (Fig.…”
Section: Symbolic Description and Layer Orientationmentioning
confidence: 99%
See 2 more Smart Citations